Fabrication of a closed hollow obturator by digital technologies: Technical report - Gomes,Isabel (2024)
Abstract Different techniques have been described for fabricating obturators for patients with maxillary defects. The hollow bulb obturator has emerged as the treatment of choice in most patients due to its light weight, decreased stress on the underlying tissues, and decreased patient discomfort. This article presents a technique for fabricating a closed hollow bulb obturator using a laboratory scanner, computer- aided design software, and three-dimensional printing.